Life quality and institutionalized elderly’s functional capacity - Oliveira, Julia Roberta de (2014)
Objective: Analyzing the life quality (LQ) and the institutionalized elderly’s functional capacity (FC). Materials and Methods: It was consisted an example of 20 elderly, institutionalized, and it was verified the LQ and the FC. Results: It was verified satisfactory scores of LQ and FC among the elderly analyzed, but this sample was based in its exclusion criteria. Conclusion: these aged people showed satisfactory levels of LQ and FC, however it is suggested new evaluation resources of LQ and FC about these people.